Evaluation of outsourcing alternatives under fuzzy environment for waste management - Kaya, Ihsan (ELSEVIER SCIENCE BV, 2012)
Production and use of electrical and electronic equipment (EEE) have been clearly increased over the last years. This has led to huge amounts of waste of electrical and electronic equipment (WEEE). The management of WEEE is a very critical and important not only for waste treatment but also to recover of valuable materials. Waste electrical and electronic equipment (WEEE or E-waste) must be disposed of properly to reduce waste, to protect the environment from hazardous materials and to obtain more useful materials in recycling. The importance of management of WEEE has become clearer in the last years and it is expected that quantities of WEEE will increase. Therefore, the management of WEEE is a critical and important decision. This paper analyzes an outsourcing decision for the management of WEEE by using a fuzzy multicriteria decision making approach. As outsourcing decisions are often based on multi criteria approaches and group decisions, this paper proposes a methodology based on fuzzy group decision making approach to evaluate and to select the appropriate WEEE outsourcing firm in Istanbul, Turkey. The selected firm will control the management of WEEE process that is the collection, transportation, processing, recycling or disposal of electrical and electronic equipment (EEE). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Waste electrical and electronic equipment; Fuzzy; Decision making; Outsourcing; ANALYTIC HIERARCHY PROCESS; ELECTRONIC EQUIPMENT WEEE; SELECTION; LOCATION; PLASTICS; SYSTEM; PLANTS; SPAIN; AHP; Engineering; Environmental Sciences & Ecology